The effect of communication, welfare and team work on the performance of youth and sports services kerinci district - Wazirman Wazirman; Tri Wahyu Ningsih; Rizka Yunita; Arina Gusti Yosika; Neni Suparwanti (Global Econedu, 2021)
This study aims to see the effect of (1) Communication on the performance of the Youth and Sports Office of Kerinci Regency (2) Welfare on the performance of the Youth and Sports Office of Kerinci Regency (3) Team Work on the performance of the Youth and Sports Office of Kerinci Regency (4) Communication, Welfare and Team Work have a joint effect on the performance of the employees of the Youth and Sports Office of Kerinci Regency.The population in this study is all There are 33 employees of the Kerinci Regency Youth and Sports Office. Technique of determining the number of samplesusing total sampling. The data analysis technique used multiple regression by fulfilling the requirements of the classical assumption test of normality, and multicollinearity, heteroscedasticity.The results of this study indicate that (1) Communication has a positive significant effect on the performance of the Kerinci District Youth and Sports Office (2) Well-being give a positive influence on the performance of the employees of the Youth and Sports Office of Kerinci Regency (3) Teamwork provide a positive influence on the performance of the employees of the Youth and Sports Office of Kerinci Regency (4) Communication, Welfare and Team Work jointly have a positive effect on the performance of the employees of the Youth and Sports Office of Kerinci Regency.